Contrasting seasonal responses of sulfate aerosols to declining SO2 emissions in the Eastern U.S.: Implications for the efficacy of SO2 emission controls. Issue 1 (5th January 2017) - Paulot, F.; Fan, S.; Horowitz, L. W.
Abstract: Stringent controls have reduced U.S. SO2 emissions by over 60% since the late 1990s. These controls have been more effective at reducing surface SO 4 2 − in summer (June, July, and August) than in winter (December, January, and February (DJF)), a seasonal contrast that is not robustly captured by Climate Model Intercomparison Project 5 global models. We use the Geophysical Fluid Dynamics Laboratory AM3 chemistry‐climate model to show that oxidant limitation during winter causes SO 4 2 − (DJF) to be sensitive to primary SO 4 2 − emissions, in‐cloud titration of H2 O2, and in‐cloud oxidation by O3 . The observed contrast in the seasonal response of SO 4 2 − to decreasing SO2 emissions is best explained by the O3 reaction, whose rate coefficient has increased over the past decades as a result of increasing NH3 emissions and decreasing SO2 emissions, both of which lower cloud water acidity. The fraction of SO2 oxidized to SO 4 2 − is projected to keep increasing in future decades, delaying improvements in wintertime air quality. Key Points: Observed weaker decline of sulfate in DJF than in JJA in response to SO2 emission controls in the U.S. is not well captured by CMIP5 models This seasonal contrast results from faster in‐cloud oxidation of SO2 by ozone, promoted by diminishing cloud acidity Anthropogenic ammonia indirectly reduces the effectiveness of SO2 emission controls in decreasing sulfate in winter